1992
DOI: 10.1002/ajh.2830390406
|View full text |Cite
|
Sign up to set email alerts
|

Binding and suppressive activity of human recombinant ferritins on erythroid cells

Abstract: We studied the relation between ferritin cellular binding and suppressive activity of recombinant H- and L-ferritin on human erythroid cells at different proliferation/differentiation phases. L-ferritin failed to show any suppressive activity or detectable binding to erythroblasts at any stage of maturation. In contrast, H-ferritin demonstrated binding to erythroblasts derived from peripheral BFU-E cells which increased steadily between 7-14 days of culture up to 15,000 molecules per cell. Reticulocytes and er… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1994
1994
1999
1999

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 35 publications
(22 reference statements)
0
9
0
Order By: Relevance
“…The role of ferritin-binding proteins(s) is uncertain; however, it has been suggested that ferritin-binding proteins may serve as acquired receptors for ferritin itself. This view is increasingly attractive in light of recent reports documenting the presence of ferritin receptors on the surface of cells (8 -12) and the suggested role of this interaction in numerous functions, including suppression of myelopoesis (13), suppression of lymphocyte proliferation (14), and facilitation of iron uptake (11). In order to begin to study the role of ferritin-binding proteins and their potential relationship to ferritin receptors, we have purified a ferritin-binding protein from human serum.…”
mentioning
confidence: 99%
“…The role of ferritin-binding proteins(s) is uncertain; however, it has been suggested that ferritin-binding proteins may serve as acquired receptors for ferritin itself. This view is increasingly attractive in light of recent reports documenting the presence of ferritin receptors on the surface of cells (8 -12) and the suggested role of this interaction in numerous functions, including suppression of myelopoesis (13), suppression of lymphocyte proliferation (14), and facilitation of iron uptake (11). In order to begin to study the role of ferritin-binding proteins and their potential relationship to ferritin receptors, we have purified a ferritin-binding protein from human serum.…”
mentioning
confidence: 99%
“…However, in other cell types, ferritin receptors are now postulated to be involved in cellular activation and proliferation (14). More specifically, it has been proposed that an H-ferritin-specific receptor is expressed on lymphocytes which downregulates cellular proliferation (12).…”
Section: Introductionmentioning
confidence: 99%
“…It is a globular protein made up of 24 subunits of two different subunit types, H or heavy (21 kD) and L or light (19 kD) (5). A specific membrane-bound receptor for tissue ferritin has been described previously in a variety of different cells and tissues including rat and human hepatocytes, pig liver, guinea pig reticulocytes, human placenta, various tumor cell lines, and lymphocytes (6)(7)(8)(9)(10)(11)(12). The precise physiological function of the ferritin receptor is unclear, however it has been suggested that the ferritin receptor on hepatocytes acts to scavenge tissue ferritin from the circulation (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…ELISA assays based on these reagents proved highly specific and useful for analysis of H-Ft distribution in body fluids and homogenates of tissues or cultured cells (15,17). Several studies showed that H-Ft has several important biological functions such as the regulation of iron metabolism (5), of cell proliferation (7)(8)(9)(10) and as an antioxidant agent (23). The lowest H-Ft concentration previous assays could detect was 5 µg/l (12) being much less sensitive than the assays for L-type ferritin.…”
Section: Discussionmentioning
confidence: 99%
“…The H-Ft and the L-Ft subunits are functionally distinct: the L-chain favors iron accumulation and mineralization without an apparent enzymatic activity (1), while the H-chain has a ferroxidase activity, accelerates iron oxidation and incorporation and, probably, participates in the regulation of iron homeostasis (5,6). In addition H-Ft suppresses in vitro cell proliferation and colony formation of hematopoietic progenitor cells (7)(8)(9)(10), and its expression is regulated by cytokines and hormones (11), supporting the hypothesis that it may have regulatory functions. The molecule is of interest in cell biology and cancer research and its study and measurement in different tissues and cultured cells is important to define its biological and clinical significance.…”
Section: Introductionmentioning
confidence: 92%